(untitled) (International Journal of Engineering and Computer Science, 2017)
This paper presents study on the market of Windows8. How it integrates both desktop and mobile. Our work in this paper is the study of Windows 8 for desktop, Windows 8 for mobile and business model of Windows8. At the end we have concluded the merits and demerits of windows8 desktop and mobile on basis of our study. Also, how Windows8 is better than its predecessors